A monolithic, low-noise, capacitive readout interface circuit for CMOS-MEMS resonator-based gravimetric chemical gas sensors - Sutri, N.Y. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents a monolithic, low-noise capacitive readout interface circuit for CMOS-MEMS resonator based gravimetric chemical gas sensors. In these sensor devices, where the sense capacitances are usually very weak, the readout interface circuit plays a crucial role in determining the overall sensor performance. Noise is observed in various active and passive devices affecting circuit performances. Particularly at low frequencies, flicker noise is dominant in degrading the quality of output signals. A dual stage, open-loop continuous time voltage sensing with chopper stabilization technique is proposed in this work to cope with it and improve the total output signal SNR. The proposed circuit is designed based on MIMOS 0.35 Î¼m AMS 3.3V CMOS technology. Cadence Spectre circuit simulator simulation results show, the proposed circuit achieves an input inferred noise of 11.6 n V/âHz, total gain of 48.1 dB and consumes a total power of 3.385 mW. The designed circuit is able to detect minute capacitance changes as low as 0.0365 aF with total sensitivity of 67.95 Î¼V/aF. Â© 2015 IEEE.